Sistem Pendukung Keputusan berbasis Web untuk Evaluasi Kinerja Pelayanan Kantor Camat Terbaik di Indonesia - Faturrohim, Aulia; Siddik, Mohd; Azmi, Sri Rezeki Maulina (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Excellent service is a service provided by the government to meet the needs of the community according to applicable regulations. Low quality of service can reduce public trust in the government. This study aims to build a web-based decision support system to assess the performance of the best sub-district offices objectively and transparently. The system development uses a waterfall model, which consists of stages of analysis, design, implementation, and testing. The analysis is carried out by collecting system requirements and determining seven assessment criteria: facilities and infrastructure, accountability, administration, performance, innovation and creativity, information systems, and preservation of customs and culture. At the design stage, use case diagrams and flowcharts are created, while implementation is carried out by building a web-based system that applies the SAW method. Testing is carried out using the black-box method to ensure the system runs well without errors. The results of our findings are in the form of a decision support system that identifies Kisaran Timur District as the district with the best performance, with a score of 0.896. The test results prove that the system functions optimally, transparently, and accurately. With this system, objectivity and transparency in assessing the performance of sub-district offices can be increased. In addition, this system helps the government in identifying superior sub-district offices and those that need improvement in order to improve the quality of public services.